Improving the delivery of social protection through ICT case studies in Mongolia, Nepal, and Vietnam. (Sustainable development working papers., 2017)
This working paper makes a case for investing in ICT to improve the delivery services of social protection programs. ICT for social protection will improve efficiency, transparency, and empower citizens by opening up areas of information and social engagement that can influence policies and resources devoted for social protection. Some of the enabling factors for faster take up of ICT in social protection programs are present in Mongolia, Nepal, and Viet Nam.